2012
DOI: 10.1073/pnas.1205653109
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic characterization of isolated candidate vertebrate magnetoreceptor cells

Abstract: Over the past 50 y, behavioral experiments have produced a large body of evidence for the existence of a magnetic sense in a wide range of animals. However, the underlying sensory physiology remains poorly understood due to the elusiveness of the magnetosensory structures. Here we present an effective method for isolating and characterizing potential magnetite-based magnetoreceptor cells. In essence, a rotating magnetic field is employed to visually identify, within a dissociated tissue preparation, cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
83
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 49 publications
4
83
1
2
Order By: Relevance
“…5 A-C). The morphology of these cells mirrored those previously reported, each with a notable opaque structure associated with the membrane (25). Assessment of their magnetic moment revealed that they vary between 2 and 152 fAm 2 , and have a profile consistent with the presence of remanence-bearing particles ( Fig.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…5 A-C). The morphology of these cells mirrored those previously reported, each with a notable opaque structure associated with the membrane (25). Assessment of their magnetic moment revealed that they vary between 2 and 152 fAm 2 , and have a profile consistent with the presence of remanence-bearing particles ( Fig.…”
Section: Resultssupporting
confidence: 60%
“…S3 and Table S1). These results are analogous to those obtained by Eder et al, who observed cells with moments spanning 4-100 fAm 2 , with the majority (11 of 13) between 10 and 50 fAm 2 (25). To establish whether the cells possess remanent magnetism or alternatively superparamagnetism, we determined the moment at a variety of different magnetic intensities (0.5, 1, 1.25, 1.5, 1.75, and 2 mT).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations